California Democratic Council Statewide Convention at Hacienda Inn - Watkins, Howard::::::::: (1982)
Keynote speaker U.S. Senator Ted Kennedy receiving standing ovation after speaking, back of Lia Triff Belli; Wally Albertson on far right